In the Beginning Were Words: Aboriginal People and the Franchise. Issue 4 (2nd October 2018) - Cooper, Jan
ABSTRACT: This article addresses confusion about when Aboriginal people gained the right to vote at both New South Wales (NSW) and Commonwealth elections in the twentieth century. All NSW Aboriginal men had the right in the nineteenth century, but some lost it at both NSW and Commonwealth levels soon after Federation. Though the losses derived from legislation, archival sources reveal that secretive official interpretations of words in the legislation were influential. Underlying them was the demand that Aboriginal people behave or look more like "us", though, unlike the Commonwealth's, NSW's exclusion was not overtly based on race or colour. Residents of Aboriginal mission stations were deemed to be residents of "charitable institutions" and therefore ineligible to vote at NSW elections; people deemed to have more than half Aboriginal "blood" were regarded as "aboriginal natives" and were therefore ineligible to vote at Commonwealth elections. Those deemed ineligible regained their rights to vote much earlier than is generally recognised, in 1926 and 1949. An Aboriginal woman's memoir shows how, by the 1930s, the exclusions could sting and how the restored right was not always welcomed by those who had experienced segregation, exclusion from Commonwealth social services, and control by officials and police.